Soy Isoflavone Genistein Impedes Cancer Stemness and Mesenchymal Transition in Head and Neck Cancer through Activating miR-34a/RTCB Axis - Hsieh, Pei-Ling (Nutrients, 2020)
Genistein, a soy-derived phytoestrogen, has been shown to exhibit anti-neoplastic activities in various cancers. Nevertheless, its effects on the elimination of tumor-initiating cells of head and neck cancer (HNC-TICs) remain unclear. Here, we investigated the inhibitory effect of genistein on HNC-TICs and potential mechanisms. Our results demonstrated that genistein lowered the proliferation of HNC-TICs by examining the percentage of ALDH1+ or CD44+ cells. Aside from the downregulation of epithelial-mesenchymal transition (EMT) in HNC-TICs, genistein restricted their tumor propagating capacities in a dose-dependent fashion. Moreover, genistein potentiated cell death caused by three commonly used chemotherapeutic agents (doxorubicin, cisplatin, and 5-FU). Our findings proved that genistein induced ROS production through upregulation of miR-34a, leading to apoptosis in HNC-TICs. The genistein-elicited miR-34a reduced self-renewal, migration, invasion capacities and ALDH1 activity, which may be partly owing to the repression of EMT. Furthermore, we showed that RTCB was a novel target that was negatively regulated by miR-34a and involved in the tumor repressive effect of genistein. Besides, the in vivo study validated that genistein retarded tumor growth through the elevation of miR-34a and suppression of RTCB. These results suggested that genistein-induced miR-34a contributed to the ROS-associated apoptosis and diminished stemness properties via repression of RTCB in HNC-TICs.